Structural characterization, biological activities, and rheological behavior of an exopolysaccharide from tea-bacteria Herbaspirillum sp. S-1 - Xuedong Chen; Guoqiang Chen; Mengjiao Li; Zixiang Liu; Wenxue Dai; Fan Wang; Haibo Zhang; Fei Liu; Youshuang Zhu (Carbohydrate Polymer Technologies and Applications)
The investigation of polysaccharides derived from microorganisms is significant due to the exceptional advantages offered by microbial exopolysaccharides (EPSs). We explored the isolation, purification, preliminary structure characterization, and potential applications of an exopolysaccharide (HS, 6.68 g/L) produced by Herbaspirillum sp. S-1. Through DEAE Sepharose fast flow column chromatography and Sephacryl S-200, we obtained a single fraction of the exopolysaccharide (S-1). Monosaccharide composition analysis revealed that S-1 mainly consisted of D-mannose, D-glucose, and D-galactose, with an average molecular weight of 4.995 × 103 g/mol, respectively. Further analyzes indicated that the main chain repeating unit of S-1 was →4)-α-D- Manp-(1→6)-β-D-Galp-(1→3)-α-D-Glcp-(1→6)-β-D-Galp-(1→3)-α-D-Glcp-(1→6)-β-D-Galp-(1→. Moreover, the in vitro determination of antioxidant activities demonstrated that S-1 exhibited notable antioxidant properties, with ∼85.6 %. S-1 has high activity in inhibiting α-glucosidase (∼52.79 %) and α-amylase (∼46.26 %). HS and S-1 exhibited anti-proliferative effects on HT-29 and BEL-7402 cells, whereas S-1 had higher anti-proliferative activity than HS. Furthermore, it exhibited good synergistic thickening performance with sclerotium gum. Consequently, the S-1 exopolysaccharide has potential for application as a natural antioxidant and additive in functional food and related industries.